2007
DOI: 10.1021/jf063210p
|View full text |Cite
|
Sign up to set email alerts
|

Anhydrous Goat's Milk Fat:  Thermal and Structural Behaviors Studied by Coupled Differential Scanning Calorimetry and X-ray Diffraction. 2. Influence of Cooling Rate

Abstract: Crystallization and melting properties of triacylglycerols (TGs) in anhydrous goat's milk fat (AGMF) are investigated by X-ray diffraction as a function of temperature (XRDT) coupled with high-sensitivity differential scanning calorimetry (DSC), using synchrotron radiation and Microcalix. The polymorphic behavior of AGMF was monitored by varying the cooling rates between 5 and 1 degrees C/min from 45 to -20 degrees C with their subsequent melting at 1 degrees C/min. Quenching of AGMF at -20 degrees C was also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 17 publications
(49 reference statements)
0
9
0
Order By: Relevance
“…The types of TAGs and fatty acids in milk fat depend on the season and the geographical regions where cows are grown, , and these variations, albeit small, can strongly affect crystallization behavior. , Compositional differences in milk fats obtained from different animals (e.g., buffalo vs cow) are more significant than variation within the same species. , Those differences are currently not fully characterized, but they could have a significant effect on the crystallization and melting behavior of milk fat, as shown by a small number of crystallization studies carried out on nonbovine milk fat, such as goat and camel. …”
Section: Introductionmentioning
confidence: 74%
“…The types of TAGs and fatty acids in milk fat depend on the season and the geographical regions where cows are grown, , and these variations, albeit small, can strongly affect crystallization behavior. , Compositional differences in milk fats obtained from different animals (e.g., buffalo vs cow) are more significant than variation within the same species. , Those differences are currently not fully characterized, but they could have a significant effect on the crystallization and melting behavior of milk fat, as shown by a small number of crystallization studies carried out on nonbovine milk fat, such as goat and camel. …”
Section: Introductionmentioning
confidence: 74%
“…β-Carotene showed several sharp peaks, indicating crystallinity, while AMF possesses smaller and broader peaks, indicating that AMF has mixed morphology at room temperature. It has previously been suggested that amorphous morphology is dominant, but the crystalline structure is also present in AMF at room temperature . For NLCs loaded with β-carotene, because Tween 80 is a noncrystalline compound at ∼20 °C, the smooth XRD curve of the β-carotene-loaded NLCs and its similarity to the spectrum of AMF suggest that β-carotene was embedded in NLCs .…”
Section: Resultsmentioning
confidence: 93%
“…It has previously been suggested that amorphous morphology is dominant, but the crystalline structure is also present in AMF at room temperature. 37 For NLCs loaded with β-carotene, because Tween 80 is a noncrystalline compound at ∼20 °C, 38−40 the smooth XRD curve of the β-carotene-loaded NLCs and its similarity to the spectrum of AMF suggest that β-carotene was embedded in NLCs. 41 Detailed structures of AMF crystals however were not studied in the present work, because it requires temperaturecontrolled small-angle XRD.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…A). The chain packing is deduced from the repetition distance corresponding to the first reflections observed at small angle (double‐chain length 2L: 40–45 Å and triple‐chain length 3L: ∼60 Å) . These configurations depended on the fatty acid composition of the lipid mixture.…”
Section: Resultsmentioning
confidence: 99%